The Role of Self-Esteem in Mediating Social Anxiety on Body Shaming Victims - Elfitasari, Tita; Winta, Mulya Virgonita Iswindari (Psikostudia : Jurnal Psikologi, 2022)
This study aims to (1) empirically test the influence of body shaming with social anxiety, (2) empirically test the influence of body shaming with social anxiety mediated by self-esteem. The subjects in this study were 141 undergraduate students of the Department of Aquaculture where the data collection method was carried out by chance. The research data was collected using three scales, (1) the social anxiety scale, (2) the body shaming scale, and (3) the self-esteem scale. The collected data is analyzed using regression and path analysis. The results showed that (1) body shaming affects social anxiety and (2) self-esteem mediates the influence of body shaming on social anxiety. Based on the results of this study, it is recommended to develop self-esteem because it is proven to be able to mediate the emergence of social anxiety in victims of body shaming. Penelitian ini bertujuan untuk (1) menguji secara empiris pengaruh body shaming dengan social anxiety, (2) menguji secara empiris pengaruh body shaming dengan social anxiety yang dimediasi oleh self-esteem. Subjek dalam penelitian ini adalah 141 mahasiswa S1 Jurusan Budidaya Perairan dimana metode pengumpulan data dilakukan secara kebetulan. Data penelitian dikumpulkan dengan menggunakan tiga skala, (1) skala social anxiety, (2) skala body shaming, dan (3) skala self-esteem. Data yang terkumpul dianalisis menggunakan regresi dan analisis jalur. Hasil penelitian menunjukkan bahwa (1) body shaming berpengaruh terhadap social anxiety dan (2) self-esteem memediasi pengaruh body shaming terhadap social anxiety. Berdasarkan hasil penelitian ini, disarankan untuk mengembangkan self-esteem karena terbukti mampu memediasi munculnya social anxiety pada korban body shaming.